2009
DOI: 10.1177/1403494808086986
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic variations in communication on sexuality and HIV/AIDS with parents, family members and teachers among in-school adolescents: A multi-site study in Tanzania and South Africa

Abstract: In all three sites, a substantial proportion of adolescents reported not communicating with their parents about HIV/AIDS, abstinence, or condoms. The low proportion of explained variation in sexuality communication implies that silence is common across sociodemographic subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 25 publications
14
71
1
Order By: Relevance
“…The majority chose parents as their preferred person to communicate with about sexuality because they believe that their parents/caretakers know them and understand them well since they live under one roof and spend much time together. This finding concurs with the finding of Guilamo-Ramos et al (2012) and Namisi et al (2009) which also showed that adolescents chose parents as the preferred source of information about sexual topics [26] [34]. This implies that caretakers are significant individuals to be included in any intervention aiming at reducing young people's sexual risky behaviours.…”
Section: The Preferred Person To Communicate On Sexuality Matterssupporting
confidence: 89%
“…The majority chose parents as their preferred person to communicate with about sexuality because they believe that their parents/caretakers know them and understand them well since they live under one roof and spend much time together. This finding concurs with the finding of Guilamo-Ramos et al (2012) and Namisi et al (2009) which also showed that adolescents chose parents as the preferred source of information about sexual topics [26] [34]. This implies that caretakers are significant individuals to be included in any intervention aiming at reducing young people's sexual risky behaviours.…”
Section: The Preferred Person To Communicate On Sexuality Matterssupporting
confidence: 89%
“…There have been suggestions that parents, especially mothers, should provide sexuality and education to youth in Africa (Namisi et al, 2009). An underlying assumption is that parents are knowledgeable, experienced, and willing to impart such knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, it is considered taboo for parents in many areas of sub-Saharan Africa to discuss sexual issues with their children [14,15]; instead, sex education came from extended family members or during pubertal initiation rites [16]. Due to socio-economic changes that have altered family structures and social norms, these traditional systems of communication have been uprooted, leaving a gap in children's sex education [15,[17][18][19][20].…”
mentioning
confidence: 99%
“…Historically, it is considered taboo for parents in many areas of sub-Saharan Africa to discuss sexual issues with their children [14,15]; instead, sex education came from extended family members or during pubertal initiation rites [16]. Due to socio-economic changes that have altered family structures and social norms, these traditional systems of communication have been uprooted, leaving a gap in children's sex education [15,[17][18][19][20]. While there are cultural challenges to promoting parent-child communication about sexual issues in sub-Saharan Africa, to the authors' knowledge there is no evidence that such strategies could not be as effective at reducing adolescent sexual risk behavior as has been shown in the US, particularly since youth in Africa are receptive to receiving information about sexuality from their parents [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation